Newsroom councils in search of lost times - Fidalgo, Joaquim (2013)
In April 1974, when Portugal recovered democracy and press freedom, after almost 50 years of political dictatorship that included a fierce media censorship, the elaboration of a new legal framework for the media was one of the strongest priorities. The importance granted to this issue was such that some of the rights and duties associated to media freedom were even inscribed in the fundamental law of the country – the Constitution itself. Among these rights and duties was the obligation for all media companies to have a newsroom council, elected by the journalists, with important powers regarding for example the choice of a new editor-in-chief, the hiring of new staff members or the adoption of major editorial principles and practices. The underlying ideas were that (a) in a democratic context, democracy should be practised also in the newsroom, and (b) journalists, besides owners and managers, should have a word in the internal decision processes, in order to make sure that the media meet their social responsibilities. This strong example of what we could call ‘participative democracy’ didn’t last long, at least in these terms. With the successive changes that brought the country closer to the general political model of European western democracies, newsroom councils kept their place but lost some of their powers and, therefore, many journalists felt less and less motivated to actively engage with them. In this paper, we intend to make a brief historical description of the changes that allegedly weakened the role of the newsroom councils, in spite of their potential as a means of media accountability and of press self-regulation. In a second moment, we’ll present the results of a survey among the existing newsroom councils of national news media, in order to try to understand the consequences of these legal changes in what regards journalists’ participation in the editorial process. Furthermore, we intend to find out if such changes altered the balance of power within media companies, opening the way to a more market-driven management and devaluating the active contribution of journalists to the editorial decisions.